A new series of 3D lanthanide phenoxycarboxylates: synthesis, crystal structure, magnetism and photoluminescence studies. Issue 23 (25th May 2021) - Sen, Rupam; Paul, Sanchayeeta; Sarkar, Alolika; Botas, Alexandre M. P.; Carneiro Neto, Albano N.; Brandão, Paula; Lopes, Armandina M. L.; Ferreira, Rute A. S.; Araújo, João P.; Lin, Zhi
Abstract : A new series of 3D Ln-carboxylates was synthesized, where the Tb one shows antiferromagnetic coupling and the Dy one shows ferromagnetic interaction, and with emission spectra combining the intra-4f emission of the Ln ions and that of the ligand. Abstract : A new series of 3D lanthanide (Ln) frameworks has been synthesized with the general formula [{Ln(L )(H2 O)}·H2 O] n (where Ln = La(1 ), Tb(2 ) and Dy(3 ); L = (HO)OC6 H2 (CH2 COO)2 ; H3 L = 2, 5-dihydroxy-1, 4-benzenediacetic acid = DHBDA). All the crystals were analyzed by single crystal X-ray diffraction. The Ln ions are octa-coordinated having the square antiprism geometry with the D 4d symmetry and connected along the crystallographic a -axis forming a zigzag chain. These chains are further connected by the ligands in three-dimensional crystallographic space. Compounds 2 and 3 were subjected to variable temperature magnetic susceptibility measurements and photoluminescence studies. Magnetic studies reveal that compound 2 possesses antiferromagnetic coupling whereas compound 3 shows ferromagnetic interaction at temperatures above ca. 40 K. The emission spectra of compounds 2 and 3 combine the intra-4f emission of the Ln ions with that of the ligand, depending on the selected temperature, pointing out that the energy transfer processes are thermally activated. In addition, compound 2 presented an invariant 5 D4 lifetime behaviour at temperatures between 15 and 300 K. Theoretical analysis showed that the long-lived lifetimes of the free ligand's excited states and the intramolecular energy transfer rate invariability are responsible for such abnormal behaviour.